Analisis Kemacetan Lalu Lintas Di Jalan Kapten Halim Kelurahan Nagri Kidul Kecamatan Purwakarta - Esti; Adi Subandi; Deny Ernawan (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2022)
The highway is an important factor for the development of human life, because the development of roads and the development of human life affect each other. Increased congestion on urban roads and roads outside the city due to increased vehicle ownership, limited traffic resources. The purpose of this study was to determine the cause of traffic jams that occurred on Halim Street, Nagri Kidul Village, Congestion of Purwakarta. After obtaining the volume data that occurred at peak hours, a traffic analysis was carried out based on the guidelines of the Indonesian Road Capacity Manual (MKJI, 1997) to determine side barriers, capacity levels and degrees of saturation on the Jalan Captain Halim, Nagri Kidul Subdistrict, Purwakarta District. The results of the analysis show that congestion is caused by the presence of street vendors on the shoulder of the road and the road divider is used by the market parking lot. With high side barriers (M), the total value of events reaches 300-499 events/hour. On the Jalan Captain Halim, Nagri Kidul Subdistrict, Purwakarta Subdistrict, the traffic volume value reaches 1394,4 pcu/hour with a road capacity for 2 directions which is 1975,509 pcu/hour and has a degree of saturation obtained 0,7058.